Link ATM Bank Syariah ke Bank Konvensional Perspektif Syariah (Studi Kasus Pada Bank Muamalah Indonesia Cabang Yogyakarta) - Albertus Maria Setyastanto (Journal Of Communication Education, 2017)
AbstractThis research is about an analysis toward ATM link between Syariah bank, especially Bank Muamalat Indonesia (BMI) and conventional bank in Islamic point of view. As an Islamic bank, BMI had perform Islamic values in its overall operation. The innovation made by BMI, ATM link between BMI and BCA, makes many inquiries from the society, especially academician wheter the product of this ATM link compliance to Syariah rules or not. It is a qualitative research used library as source of datas. It applies content analysis as method of analysis. The research found that the A7M link product between BMI and BCA is compliance to Syariahc rules. BMI cooperate with two switching corporation, namely PT Artajasa and PT Rintis Sejahtera. The cooperation is based on ijarah contract, and contract of ijarah is lawful in Islam. The aim of cooperation among them is to secure benefit for human being and repell the evil. Keywords : ATM, bank syariah, bank konventional,